The Role of Servant Leadership in Developing Management Information Systems - ATHEEB, MOHAMMED KAZEM; MUSEHIBE, Dr. MOHSIN RASHID (The journal of contemporary issues in business and government, 2021)
The research aims to test the impact of servant leadership in management information systems, as well as to identify the level of servant leadership practice and management information systems in the Directorate of Communications and Information Systems in the Iraqi Ministry of Interior, in terms of the importance of the research variables to the directorate and the sample community, as the research adopted the exploratory analytical descriptive approach In his achievement, through a survey of the opinions of an intended quota sample of (266) individuals, By adopting the questionnaire as a main tool for data collection that includes (44) items divided into the two research variables, As well as conducting open interviews to identify the problems, strengths and weaknesses of the directorate about practicing the research variables, The statistical analysis of the most prominent result concluded that the Directorate of Communications and Information Systems adopted the practices of servant leadership, and was able to employ them to positively influence the development of its management information systems, and the researcher came up with a set of recommendations.